Super-Selective Partial Splenic Embolization for Hereditary Spherocytosis in Children: A Single-Center Retrospective Study - Wang, Rui-jue; Xiao, Li; Xu, Xi-ming; Zhang, Ming-man; Xiong, Qiang (Frontiers in Surgery, 2022)
Background: Hereditary spherocytosis (HS) is the most common hemolytic anemia due to erythrocyte membrane defects. Total splenectomy is the most effective treatment for moderate or severe HS. As a conservative alternative, partial splenic embolization (PSE) can preserve part of the spleen's function, thus reducing the risk of overwhelming post-splenectomy infection (OPSI) or sepsis, especially for pediatric patients. However, it is not easy to precisely control the scope of interventional embolization, limiting PSE applications. The present study aims to optimize the PSE procedure on smaller, which is named super-selective partial splenic embolization (SPSE), to improve the controllability and assess the feasibility and effectiveness of SPSE. Results: This study was conducted by retrospectively reviewing clinical data from HS patients treated by surgical treatments, which were diagnosed at the children's hospital of Chongqing medical university from January 2015 to December 2019. Patients were divided into two groups according to their treatment preference: SPSE (16 patients) group and total splenectomy (41 patients) group. The mean proportion range of splenic embolism by SPSE was 82.4%, close to the expected value (70%~85%). The average hemoglobin value increased significantly from 6.85（5.6-8.0）g/dL before SPSE to 12.4 (10.4-13.3) g/dL after SPSE (P < 0.001). All children after SPSE suffered mild postembolization syndrome, including pain, fever, and vomiting, which could easily be controlled with appropriate supportive therapy. Conclusions: SPSE is a safe and effective treatment for moderate or severe HS in children. However, with a longer follow-up, more patients further assess the value of SPSE.